The resolution of Islamic commercial disputes in Malaysia: courts, mediation and arbitration - Hassan, Rusni; Yusoff, Adnan (Singapore Mediation Centre, 2007)
Islam is the second largest religion in the world and most Muslims live in Asia. In some countries in Asia, Islamic and Shariah law prevails in commercial dealings. This article provides a brief overview of Islamic commercial law and then examines the processes by which commercials disputes can be resolved under Shariah law in Malaysia. While this article does not strictly focus on mediation, it sets the context in which mediation conducted is conducted in Shariah law. This journal hopes to publish an article focusing on such mediation in a future issue.